Association of ACEi/ARB Use and Clinical Outcomes of COVID-19 Patients With Hypertension - Ma, Jing; Shi, Xiaowei; Yu, Jiong; Lv, Feifei; Wu, Jian; Sheng, Xinyu; Pan, Qiaoling; Yang, Jinfeng; Cao, Hongcui; Li, Lanjuan (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Evidence has shown that angiotensin-converting enzyme 2 (ACE2), which can be upregulated after ACEi and ARB treatment, may play a dual role in the pathogenesis and progression of COVID-19. We aimed to assess the association between the use of ACEi/ARB and the outcome of COVID-19 patients with pre-existing hypertension in non-endemic areas. Methods From 17 January 2020 to 19 February 2020, 286 patients with hypertension were enrolled in this retrospective study out of 1437 COVID-19 patients from 47 centers in Zhejiang and Jiangsu Province. The composite endpoints consisted of mechanical ventilation, ICU admission, or death. Cox proportional hazards analysis was performed to assess the association between ACEi/ARB and clinical outcomes of COVID-19 patients with hypertension. Results In the main analysis, 103 patients receiving ACEi/ARB were compared with 173 patients receiving other regimens. Overall, 44 patients (15.94%) had an end-point event. The risk probability of crude endpoints in the ACEi/ARB group (12.62%) was lower than that in the non-ACEi/ARB group (17.92%). After adjusting for confounding factors by inverse probability weighting, the results showed that the use of ACEi/ARB reduced the occurrence of end events by 47% (HR = 0.53, 95% CI, 0.34 to 0.83). Similar results were obtained in multiple sensitivity analysis. Conclusions In this retrospective study, among COVID-19 patients with hypertension, the use of ACEi/ARB is not associated with an increased risk of disease severity compared with patients without ACEi/ARB. The trends of beneficial effects of ACEi/ARB need to be further evaluated in randomized clinical trials.